Evaluation of the corrosion resistance of a new AlSi10MnMg(Fe) secondary alloy. (2019) - Berlanga, C.; Bakedano, A.; de Ciriza, A. Perez; Rivero, P.J.; Mendez, S.; Rodriguez, R.; Niklas, A.
Abstract: In this work the corrosion resistance of a new AlSi10MnMg(Fe) secondary alloy is evaluated as a function of the wall thickness obtained by high pressure die-casting (HPDC) in comparison with a primary alloy. The electrochemical tests have been performed at two different saline concentrations (0.03 and 0.5 M NaCl, respectively) in order to determine the corrosion rate. The experimental results indicate that there are not significant differences in the corrosion rate as well as pitting corrosion for both primary and secondary alloys. Finally, SEM/EDS microanalysis has confirmed that the corrosion mechanism is preferentially through the eutectic areas